General Voting – equality or privilege - Manolov, Georgi L. (Sociološki pregled, 2021)
This article looks at the role and place of General Voting as a key ingredient for the democratic political process. This right is interpreted as a part of the very essence of equality in general and as a basic foundation of political democracy in particular. In this context, there is the issue about privileges in politics, which regardless of their regulation are becoming increasingly established as a legal barrier to the realization of complete political equality. Some proposals have been also made to limit political privileges in the democratic state.